Screening Bioactive Compounds of Siraitia grosvenorii by Immobilized β2-Adrenergic Receptor Chromatography and Druggability Evaluation - Jia, Xiaoni; Liu, Jiajun; Shi, Baimei; Liang, Qi; Gao, Juan; Feng, Gangjun; Chang, Zhongman; Li, Qian; Zhang, Xiaohong; Chen, Jianbo; Zhao, Xinfeng (Frontiers in Pharmacology, 2019)
As the first and key step of traditional Chinese medicine (TCM) guided drug development, lead discovery necessitates continuous exploration of new methodology for screening bioactive compounds from TCM. This work intends to establish a strategy for rapidly recognizing β2-adrenergic receptor (β2-AR) target compounds from the fruit of Siraitia grosvenorii (LHG). The method involved immobilization of β2-AR onto amino-microsphere to synthesize the receptor column, the combination of the column to high performance liquid chromatography (HPLC) to screen bioactive compounds of LHG, the identification of the compounds by HPLC coupled with mass spectrometry (MS) and the evaluation of druggability through pharmacokinetic examination by HPLC-MS/MS. Mogroside V was screened and identified as the β2-AR targeted bioactive compounds in LHG. This compound exhibited desired pharmacokinetic behavior including the time to reach peak plasma concentrations of 45 min, the relatively low elimination of 138.5 min and the high bioavailability. These parameters indicated that mogroside V has a good druggability for the development of new drugs fighting β2-AR mediated respiratory ailments like asthma. Combination of the methods in this work is probably becoming a powerful strategy for screening and early evaluating the bioactive compounds specifically binding to G-protein coupled receptors target from complex matrices including TCM.